Tradisi Pembacaan Teks-Teks Agama dan Sosiologi Dakwah Lingkungan di Lombok, Indonesia: (Studi Kasus di Bayan dan Sembalun) - Naamy, Nazar (Jayapangus Press, 2022)
In the history of Islamic development in Lombok, texts, cultures and prophecies played a significant role in the growth of environmentally friendly Islam. Religious texts, as well as sources from the Ancient Scriptures, or from the yellow books, are continuously read in some villages in Lombok. In Lombok, these two types of texts are still read and are sources of witness to local religious figures, such as Kyai and Ustadz, in Bayan and Sembalun. Among the texts read are Qashais al-Anbiya, Kitab of Fikih and the Kitab of Imam Shafi. As a village that still applies the customs and traditions of the Sasaks, Bayan and Sembalun synergize elements in the tradition with the teachings in Islam holistically. To find a form of synergy between the two, a method of dermatological research with an ethnographic approach was chosen to be used in this study. The ethnographic approach itself is a type of approach that finds in-depth data through the process of engaging observations and in- depth interviews. The leaders of Adi, Kyai, Ustad and the villagers were observed and interviewed to learn about the religious texts and the development of religious environments in Bayan and Sembalun.